Handbook of environmental and sustainable finance - Ramiah, Vikash; Gregoriou, Greg N. 1956 (London, UK Academic Press, an imprint of Elsevier, 2016)
This book summarizes the latest trends and attitudes in environmental finance, balancing empirical research with theory and applications. It presents an intellectually cohesive examination of problems, opportunities, and metrics worldwide.
Section 1. Environmental regulations post the Kyoto Protocol on climate change. Climate change and Kyoto Protocol : an overview Anil Gupta Environmental policies post the Kyoto Protocol on climate change : evidence from the US and Japan Vikash Ramiah, Michael Gangemi, Min Liu Efficiency of U.S. state EPA emission rate goals for 2030 : a data envelopment analysis approach Greg N. Gregoriou, Vikash Ramiah -- Section 2. Environmental economics. Environmental water governance in the Murray-Darling Basin of Australia : the movement from regulation and engineering to economic-based instruments Claire Settre, Sarah Ann Wheeler Damages evaluation, periodic floods, and local sea level rise : the case of Venice, Italy Massimiliano Caporin, Fulvio Fontini Corporate social responsibility and macroeconomic uncertainty Abraham Lioui Public value of environmental investments : a conceptual outlook on the management of normatively determined risks Camillo von Mèuller, Steven A. Brieger What holds back eco-innovations? : a "green growth diagnostics" approach Harald Sander Trade openness and COb2s emission : evidence from a SIDS Raja Vinesh Sannassee, Boopen Seetanah Will TAFTA be good or bad for the environment? Dhimitri Qirjo, Robert Christopherson Feminism, environmental economics, and accountability Tehmina Khan -- Section 3. Environmental/sustainable finance. Does national culture affect attitudes toward environment friendly practices? Kartick Gupta, Ronald McIver The economic and financial effects of environmental regulation Imad A. Moosa Environmental challenges and financial market opportunities Colin Read Environmental finance John Anderson The relationship between screening intensity and performance of socially responsible inventment funds Philip Gharghori, Elizabeth Ooi Using COb2s emission allowances in equity portfolios Michael Graham, Anton Hasselgren, Jarkko Peltomèaki The returns from investing in water markets in Australia Sarah Ann Wheeler, Peter Rossini, Henning Bjornlund, Belinda Spagnoletti Product market competition and corporate environmental performance Kartick Gupta, Chandrasekhar Krishnamurti -- Section 4. Funding and accounting systems. The costs and benefits of cost--benefit analysis as applied to environmental regulation Imad A. Moosa The crowdfunding of renewable energy projects Davide Bonzanini, Giancarlo Giudici, Andrea Patrucco Management accounting and biodiversity : the cultural circuit of capitalism and the social construction of a perfect market? Gillian Vesty, Albie Brooks, Judy Oliver, Sukanta Bakshi.
Includes bibliographical references and index.
Keywords: Environmental economics; Finance -- Environmental aspects; Environmental policy; Sustainable development -- Finance; Climate change mitigation -- Economic aspects